Accuracy of Location Identification by GPS and Possibilities for its Application in Agriculture - Pázmányi, Sándor; Dobos, Attila; Pajna, Sándor (Acta Agraria Debreceniensis, 2004)
A description of the design and operating principle of the GPS system and the explanation of key terms of telemetric and chronometric measurements is followed by several examples characteristic of the results of factors which may influence accuracy of the identification of geographic location by satellites. In addition, results of accuracy testing of absolute GPS measurements and improvements of accuracy experienced and attributable to the alteration of the periods used for establishing average values are highlighted. Furthermore, we examined certain practical possibilities for the use of GPS systems in agriculture, emphasizing the advantages hidden in the use of GIS-GPS integration, crop mapping, soil maps and gross produce maps, in the application of the VRT (Variable Rate Technology) and in combinations of the same.